Sex-Dependent Effects of Chronic Social Defeat on Emotional and Social Behaviors, and Parameters of Oxytocin and Vasopressin Systems in Mandarin Voles (Microtus mandarinus) - Wenjuan Hou; Huan Ma; Yufeng Xun; Xin Zhang; Wenqi Cai; Shuying Huang; Zhixiong He; Fadao Tai; Rui Jia (Frontiers in Neuroscience, 2021)
In the regulation of emotional and social behaviors, both oxytocin (OT) and vasopressin (AVP) are sex specific. Although significant sex differences have been reported in the context of behavioral and hormonal responses to social stress, such differences in response to chronic social defeat stress (CSDS) and the underlying neural mechanisms remain largely unknown. By investigating monogamous mandarin voles (Microtus mandarinus), CSDS was found to decrease the percentages of time spent in the central area of the open field, in the open arms of the elevated plus maze, as well as in the light area of the light and dark boxes in both male and female voles. CSDS also increased the observed level of social withdrawal in both sex groups. However, CSDS exposure increased the percentages of immobile time in both the tail suspension test and the forced swim test and reduced the locomotor activity in the open field (in females only). Along with these behavioral changes, the oxytocin receptor (OTR) levels in the nucleus accumbens (NAc) were significantly lower in CSDS-exposed voles of both sexes; however, in males, the levels of OTR in the paraventricular nucleus (PVN) were reduced. CSDS-exposed males showed lower levels of V1aR in the NAc than CSDS-exposed females. Furthermore, induced by a single social defeat event, CSDS reduced c-Fos and OT double labeling in the PVN of females but increased c-Fos and AVP double-labeled neurons in the PVN of males exposed to a single social defeat event. Collectively, the present study indicates that OT and AVP systems may play important regulatory roles in the sex differences of behavioral performances in response to CSDS. These findings suggest mandarin voles as a useful animal model for studying sex-specific behavioral performance and the underlying neurobiological mechanisms of stress-related mental disorders in preclinical studies.